Analisis Pengaruh Jumlah Uang Beredar (M2) dan Tingkat Suku Bunga Terhadap Inflasi di Indonesia Tahun 2008-2022 - Joufrean Gefran Nangoy; Een N. Walewangko; Audie O. Niode (PT. Hasba Edukasi Mandiri, 2025)
Inflation is the process of continuously increasing the prices of general goods. An increase in the price of just one or two goods is not called inflation, unless the increase extends to (or results in an increase in) most of the prices of other goods. This research aims to analyze the influence of Money Supply (M2) and Interest Rates on Inflation in Indonesia, partially or simultaneously. The method used in this research is the Multiple Linear Regression method. The results of this research state that partially the Money Supply (M2) has a positive but not significant effect on inflation, the Interest Rate has a negative and significant effect on inflation. Then simultaneously the Money Supply (M2) and the Interest Rate together have a significant influence on Inflation.